2005
DOI: 10.1002/adma.200501169
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient, Deep‐Blue Doped Organic Light‐Emitting Devices

Abstract: In recent years, there has been considerable interest in developing blue organic light-emitting devices (OLEDs) with high efficiency, deep-blue color, and long operational lifetime. The deep-blue color is defined arbitrarily as having blue electroluminescent (EL) emission with a Commission Internationale de l'Eclairage y coordinate value (CIE y ) of < 0.15. Such emitters can effectively reduce the power consumption of a full-color OLED and can also be utilized to generate light of other colors by energy cascad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
131
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(131 citation statements)
references
References 23 publications
0
131
0
Order By: Relevance
“…The data showed that distyrylarylene host DPVBi (4,4 0 -bis(2,2-diphenyl-ethen-1-yl)-diphenyl) and distyrylarylene dopant BCzVBi (4,4 0 -(bis(9-ethyl-3-carbazovinylene)-1,1 0 -biphenyl) exhibit the highest luminous efficiency and external quantum efficiency among the materials that have been reported in the literature so far. There are great progresses for device fabrication techniques and materials development in the past decade [6][7][8][9]. However, further improvements in both the efficiency and brightness for blue OLEDs are still necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The data showed that distyrylarylene host DPVBi (4,4 0 -bis(2,2-diphenyl-ethen-1-yl)-diphenyl) and distyrylarylene dopant BCzVBi (4,4 0 -(bis(9-ethyl-3-carbazovinylene)-1,1 0 -biphenyl) exhibit the highest luminous efficiency and external quantum efficiency among the materials that have been reported in the literature so far. There are great progresses for device fabrication techniques and materials development in the past decade [6][7][8][9]. However, further improvements in both the efficiency and brightness for blue OLEDs are still necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The tailored bandgap and light of an appropriate wavelength generate these electrons needed for the oxidation reaction. 44 The photocatalytic activity of msg-C 3 N 4 is increased because of a positive shift in first order constant k as a result of H 2 O 2 addition (Table S2 †). Therefore, H 2 O 2 increases the rate of hydroxyl radical production e.g.…”
Section: -37mentioning
confidence: 99%
“…Although a large number of valuable red and green emitters that satisfy the requirements for OLEDs have been developed, efficient and stable blue emitters are still rare and have been the subject of considerable interest [1,2]. Major focus has been on various material systems, including anthracene [3][4][5], distyrylarylene [6][7][8][9][10][11], fluorene [12,13] and tetra(phenyl)silyl derivatives [14,15].…”
Section: Introductionmentioning
confidence: 99%